2005
DOI: 10.1007/s10702-005-7127-4
|View full text |Cite
|
Sign up to set email alerts
|

Can a Circulating Light Beam Produce a Time Machine

Abstract: In a recent paper, Mallett found a solution of the Einstein equations in which closed tiimelike curves (CTC's) are present in the empty space outside an infinitely long cylinder of hght; moving in circular paths around an axis. Here we show that, for physically realistic energy densities, the CTC's occur at distances from the axis greater than the radius of the visible universe by an immense factor. We then show that Mallett's solution has a curvature singularity on the axis, even in the case where the intensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Thus, Godel's rotating-dust cosmological model [1] violates conditions (i,ii), as does Tipler's rotating-string solution [2]; the wormhole model by Moris, Thorne and Yurtsever [3] violates condition (iii). Gott's solution [4] of two infinitely long cosmic strings violates condition (ii) [10], and Mallett's solution [8] violates condition (i) (see [11]). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, Godel's rotating-dust cosmological model [1] violates conditions (i,ii), as does Tipler's rotating-string solution [2]; the wormhole model by Moris, Thorne and Yurtsever [3] violates condition (iii). Gott's solution [4] of two infinitely long cosmic strings violates condition (ii) [10], and Mallett's solution [8] violates condition (i) (see [11]). …”
Section: Introductionmentioning
confidence: 99%
“…These calculations demonstrated a phenomenon known as inertial frame dragging. Of further interest, in a later controversial publication, Mallet found exact solutions of the Einstein field equations and showed that the exterior metric contained closed timelike curves (CTCs) [10,11]. These light-induced CTCs are conjectured by Mallett to be the foundation for a time machine.…”
mentioning
confidence: 99%
“…Rather, as shown in Ref. [2], the light rays travel along geodesics orbiting a central line singularity.…”
Section: Introductionmentioning
confidence: 90%
“…However, Ref. [2] argues that this means that the spacetime of Ref. [1] is unlike the spacetime one would get by introducing circulating light into a flat background.…”
Section: Introductionmentioning
confidence: 99%